Effective transmetalation from gold to iron or ruthenium - Hashmi, A. Stephen K.; Molinari, Lise (Organometallics, 2011)
The transmetalation of aryl, alkynyl, and alkyl groups from organogold compounds to iron complexes offers an efficient synthesis of organoiron complexes under very mild conditions. This method could be extended to ruthenium complexes.
Gesehen am 31.08.2022